Cross-cultural validation of a questionnaire on food safety and food security in Italy - Gianfredi, Vincenza; Nucci, Daniele; Croci, Maria Chiara; Ferranti, Roberta; Stacchini, Lorenzo (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: The manuscript focuses on the translation, adaptation, and validation of Food Security Survey Module (FSSM) and Food Safety Knowledge and Behaviour (FSKB) questionnaires for use in the Italian context. Methods: The online survey was anonymously administered by Microsoft Forms to Italian adults, October-November 2023. The retest questionnaire was done 30 days after the first round. The questionnaire’s reliability was assessed using Cronbach’s α. Reproducibility was measured using Cohen’s kappa coefficient (κ), and the Kendall’s τ correlation coefficient (τ). Feasibility was assessed trough ad hoc questions. Results: A total of 96 subjects participated to the round of validation. A high level of reliability was found with standardized α of 0.91 and 0.75 for FSSM and FSKB, respectively. The mean κ was 0.669, standard error (SE= 0.019) for FSKB, and τ ranged between 0.595 and 1.000, with significant correlations (p< 0.001). Most participants (76.0%) found the questions clear, with 63.6% completing the survey in less than 10 minutes. Conclusions: The translation and validation process have yielded reliable and culturally relevant instruments for assessing food safety and food security in the Italian population. These validated questionnaires can serve as valuable tools for future research and interventions in the domain of food safety/security in Italy.